Ion density fluctuations in liquid metals: the strongly interacting ion-electron plasma - Bove, L.E.; Petrillo, C.; Sacchetti, F. (Condensed Matter Physics, 2008)
An unified description of liquid metals dynamics based on an interacting two-component model for the ionelectron plasma is tempted. The propagation velocity of the collective modes in alkali and polyvalent metals, derived from inelastic neutron and x-rays scattering experiments, is compared with the estimates obtained by different theoretical approximations for the strongly-interacting plasma. Using accurate results for the electron gas correlation energy, and taking into account the ion finite size effects, a good overall description of a large set of liquid metals is obtained. The observed trend for the damping of the collective modes in liquid metals is also discussed within the framework of the two-component description.